2012
DOI: 10.1530/joe-12-0032
|View full text |Cite
|
Sign up to set email alerts
|

Normal muscle glucose uptake in mice deficient in muscle GLUT4

Abstract: Skeletal muscle insulin resistance is a major characteristic underpinning type 2 diabetes. Impairments in the insulin responsiveness of the glucose transporter, Glut4 (Slc2a4), have been suggested to be a contributing factor to this disturbance. We have produced muscle-specific Glut4 knockout (KO) mice using Cre/LoxP technology on a C57BL6/J background and shown undetectable levels of GLUT4 in both skeletal muscle and heart. Our aim was to determine whether complete deletion of muscle GLUT4 does in fact lead t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 66 publications
0
24
0
1
Order By: Relevance
“…Moreover, Glut4 content in soleus and gastrocnemius was significantly increased in HIIT group vs. CON and interestingly, Glut4 seems to be largely involved in whole body glucose homeostasis. Several studies using muscle-specific Glut4 KO mice have shown that Glut4 disruption can lead to hyperglycaemia 47 or impaired glucose tolerance in high fat or chow-fed mice 48, 49 . Likewise, studies dealing with the effect of a single exercise session on Glut4-deficient mice, all converge upon the conclusion that Glut4 is the major factor responsible for exercise-induced glucose uptake 5052 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Glut4 content in soleus and gastrocnemius was significantly increased in HIIT group vs. CON and interestingly, Glut4 seems to be largely involved in whole body glucose homeostasis. Several studies using muscle-specific Glut4 KO mice have shown that Glut4 disruption can lead to hyperglycaemia 47 or impaired glucose tolerance in high fat or chow-fed mice 48, 49 . Likewise, studies dealing with the effect of a single exercise session on Glut4-deficient mice, all converge upon the conclusion that Glut4 is the major factor responsible for exercise-induced glucose uptake 5052 .…”
Section: Discussionmentioning
confidence: 99%
“…Fam and coworkers (2012)showed that the deletion of the skeletal muscle GLUT4 on the pure C57BL6/J background strain did not impair the whole-body glucose disposal. These authors, among others (Ryder et al 1999, Charron et al 2005, Fam et al 2012, considered that other unidentified GLUTs were upregulated in an attempt to compensate the lack of GLUT4. Probably, the previous hypothesis justifies the fact that even with lower content of plasma membrane GLUT4 in EDL and soleus, the OTR/down group did not exhibit lower glycogen concentrations when compared with the CT group (Pereira et al 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…This effect was significant for both exercise groups in olanzapine-treated rats, as levels of GLUT4 almost doubled compared to sedentary rats, which parallels the observation that both 1 h and 3 h of exercise were equally effective in mitigating glucose intolerance. As these findings are only correlational, the causal role of GLUT4 on olanzapineinduced glucose intolerance will require additional future study with techniques that directly modify expression of GLUT4, such as the muscle-specific GLUT4 knockout mouse (Fam et al, 2012). The role of GLUT4 is manifold, and its beneficial effects on insulin resistance and hyperglycemia may involve its translocation to the cell membrane in addition to increased gene and protein expression in skeletal muscle and other tissues.…”
Section: Discussionmentioning
confidence: 99%